Pytanie o gościnność w filozofii Jacques’a Derridy - Kopka, Aleksander (Folia Philosophica, 2018)
In this paper I sketch the problem of hospitality as developed by Jacques Derrida in his late work. I pinpoint the dependence between hospitality and deconstruction arguing that the hospitality is not an unexpected turn in relation to Derrida’s earlier work in deconstruction of metaphysics, but its further development on ethical and political level. Derrida keeps taking hospitality as an alternative name or an example of deconstruction, showing in this peculiar metaphor quasi-ontological structure of trace haunted by what precedes and what follows it, sabotaging its homogeneity and integrity.